Pelatihan Shooting Movie Islami Sebagai Media Pembelajaran Siswa SMP Islam Darul Muttaqin - Heri Cahyono; Iswati Iswati; Muhammad Yusuf; Umar Al Faruq A. Hasyim; Muhamad Awalludin Sidik; Rani Setyawati (CV. Creative Tugu Pena, 2021)
Community service is a medium that bridges the world of education with society where the university sends lecturers and students to the community to mingle and collaborate in dealing with problems that exist in society, especially at Daarul Mutaqin Islamic Junior High School, Metro City. The purpose of this community service is to provide understanding and skills to students and teachers related to the use of Islamic shooting as a medium for student learning to make it easier to understand and remember the values ​​contained in the material presented and the media can be felt by all parties. Keywords: Pelatihan Shooting Movie, Learning Media, Media Pembelajaran